The Effectiveness of Augmented Reality as a Learning Medium in Enhancing Students' Motivation and Their Ability to Analyze Physics Concepts - Egista*, Elfatihan; Haryanto, Haryanto; Mustofa, Hisbulloh Als (Jurnal Pendidikan Sains Indonesia, 2025)
One of the primary challenges students face in learning physics is low motivation and a limited ability to analyze physics concepts. This issue is often attributed to traditional teaching methods that heavily rely on textbooks, which may not engage students effectively. This study investigates the effectiveness of augmented reality-based learning media in enhancing students' learning motivation and their ability to analyze physics concepts. A total of 67 students were randomly selected as the research sample. The study employs a quantitative research design using a pretest-posttest approach. Data were analyzed using the N-gain test and multivariate analysis of covariance (Mancova). The findings from the N-gain test indicate a significant improvement in both students' motivation to learn and their ability to analyze physics concepts. Furthermore, the Mancova results demonstrate that augmented reality-based learning media positively influence students' final learning motivation and analytical abilities. These effects are observed after controlling for students' initial learning motivation and baseline concept analysis abilities in physics